Kepatuhan Wajib Pajak Bumi dan Bangunan Berdasarkan Wilayah Kota Binjai Menggunakan Algoritma Clustering - Malasari, Indah; Buaton, Relita; Sihombing, Anton (Jurnal Manajamen Informatika Jayakarta, 2023)
Land and Building Tax (PBB) is one type of regional tax regulated by the government in determining the amount of tax for implementation and development and increasing the prosperity and welfare of the people. Based on taxpayer compliance data at BPKPAD Kota Binjai, it shows that the more taxpayers in a region, the more data stored will also increase. From the tests carried out using the Clustering algorithm, it can be known the variables of area area, Kelurahan, Payment Status level. It is known that Cluster 1,2,3 of 518 UN mandatory data is where Cluster 1 amounts to 242 data, Area is 1,000,000 – 501,000, with Binjai Village and Payment Rate is Poor, Cluster 2 has 60 data Area is 500,000 – 251,000, with Kelurahan Suka Maju and Payment Rate is Poor and Cluster 3 is 216 data Area Area is 1,000,000 – 501,000, with Jati Negara Village and Payment Rate is Not Good.